2011
DOI: 10.1016/j.neuron.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Altered Low-Gamma Sampling in Auditory Cortex Accounts for the Three Main Facets of Dyslexia

Abstract: It has recently been conjectured that dyslexia arises from abnormal auditory sampling. What sampling rate is altered and how it affects reading remains unclear. We hypothesized that by impairing phonemic parsing abnormal low-gamma sampling could yield phonemic representations of unusual format and disrupt phonological processing and verbal memory. Using magnetoencephalography and behavioral tests, we show in dyslexic subjects a reduced left-hemisphere bias for phonemic processing, reflected in less entrainment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
268
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(302 citation statements)
references
References 76 publications
30
268
2
2
Order By: Relevance
“…For example, a proposed link between auditory processing and literacy development has implicated neural oscillation entrainment to multiple timescales [26,89,90,112]. Although still vague, this approach connects with recent ideas about the implementation of speech perception in the brain [113,114].…”
Section: (B) From Measures To Constructsmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, a proposed link between auditory processing and literacy development has implicated neural oscillation entrainment to multiple timescales [26,89,90,112]. Although still vague, this approach connects with recent ideas about the implementation of speech perception in the brain [113,114].…”
Section: (B) From Measures To Constructsmentioning
confidence: 89%
“…However, other recent neural oscillation data are inconsistent with temporal sampling at the syllable rate and call for a reinterpretation of data previously thought consistent with rapid processing [89,90]. Simplified schematic diagram of hypothetical relations among theoretical and empirical constituents of the temporal processing approaches to developmental language disorders.…”
Section: Presumed Links In a Causal Chain: What Do The Data Show?mentioning
confidence: 95%
“…The AMPH approach to speech rhythm would predict that atypical entrainment at slower rates would have consequences throughout the phonological system. Indeed, a study of adult French-speaking dyslexics (Lehongre et al 2011) has suggested atypical oscillatory entrainment to faster gamma rate (~30 Hz) amplitude modulations (these authors measured entrainment to a complex white noise stimulus linearly increasing in modulation rate between 10−80 Hz ). Using the auditory steady-state response (ASSR) as a measure of oscillatory entrainment (a power increase at the rate of stimulation), the French study found that the ASSR at 30 Hz (low gamma rate) in auditory cortex was not left-dominant in dyslexic adults, in contrast to control participants.…”
Section: Neuronal Rhythmic Entrainment and Reading Developmentmentioning
confidence: 99%
“…Studies have, however, shown that the dominant ASSR generator is determined by the modulation rate. That is, 80 Hz ASSRs are thought to be predominantly generated by brainstem sources, whereas low-frequency ASSRs (such as 4 and 20 Hz) are dominated by cortical sources (e.g., Herdman et al 2002;Lehongre et al 2011;Millman et al 2010). This idea is supported by studies in animals (e.g., Frisina et al 1990;Joris et al 2004) and in humans (e.g., Giraud et al 2000) showing that cortical neurons are more specialized than brainstem neurons to follow slow modulations.…”
Section: Introductionmentioning
confidence: 99%